Curation cost exchange platform - Faria, Luís (2014)
This demonstration proposal describes the Curation Cost Exchange platform (CCEx), a web application that allows organizations to introduce, analyse, share and compare the cost of their digital curation activities. It is also a central hub for digital curation costing related information; and is a social platform that brings together organizations with the same problems and allows sharing of experiences, good practices and know-how. The CCEx is an output of the 4C Project (a Collaboration Clarify the Costs of Curation) and the relationship of the CCEx to other 4C Project outputs will also be briefly described.